Knowledge and practice of family planning among pregnant tribal women in Southern India: an observational study - Kiranmayee Muralidhar; Holly Nishimura; Kate Coursey; Karl Krupp; Poornima Jaykrishna; Vijaya Srinivas; Purnima Madhivanan (Contraception and Reproductive Medicine, 2024)
Abstract Background There are over 700 Scheduled Tribes (ST) living in 30 Indian states. As with other indigenous groups across the world, Indian ST have some of the poorest infant and child health outcomes of any communities in India. A child born to an ST family is 19% more likely to die in the first month of life and has a 45 percent risk of dying in their first year compared with other Indian populations. Research suggests that early conception, high fertility, and low use of family planning methods are large contributors to these disparities. Methods A cross sectional survey in Kannada was conducted among 303 pregnant tribal women in Mysore, India after obtaining informed consent. Univariate and multivariable analyses were carried out to determine the demographic and psychosocial factors associated with knowledge of contraceptive methods using Stata 14.0. Results There was widespread knowledge about female sterilization, while only 39.3% of women reported hearing about one or more forms of temporary contraception, and 36.3% knew where to get them. The largest proportion of women had heard about copper-T (33.0%), followed by oral contraceptive pills (23.8%), condoms (11.9%), and injectables (4.6%). Only 2.7% of women reported ever using any form of temporary contraception. Results from the multivariable logistic regression indicated that knowledge of at least one form of temporary contraception was linked to higher age (adjusted odds ratio[AOR]: 1.09; 95% CI: 1.02, 1.17), greater number of years of marriage (AOR: 0.90; 95% CI: 0.85, 0.96), and last birth in a government facility (AOR: 3.67; 95% CI: 1.99, 6.82). Conclusions The study revealed poor knowledge and utilization of temporary contraceptive methods among a tribal population in rural Mysore, India. Interventions aiming to increase knowledge of contraceptive options are important for birth spacing in this population and should target younger women and those without contact with government health facilities.